Crystallographic structure of wild-type SARS-CoV-2 main protease acyl-enzyme intermediate with physiological C-terminal autoprocessing site - Jaeyong Lee; Liam J. Worrall; Marija Vuckovic; Federico I. Rosell; Francesco Gentile; Anh-Tien Ton; Nathanael A. Caveney; Fuqiang Ban; Artem Cherkasov; Mark Paetzel; Natalie C. J. Strynadka (Nature Communications, 2020)
The SARS-CoV-2 main protease (Mpro) is one of two cysteine proteases essential for viral replication. Here, the authors determine the crystal structure of an Mpro acyl intermediate with its native C-terminal autocleavage sequence and the structure of a product bound active site mutant (C145A), which are of interest for antiviral drug development.